Exploring Global Phenomena of Modern Islamic Culture: A Systematic Literature Review - Mohammad Izdiyan Muttaqin; S. Salahudin Suyurno (Mimbar Agama dan Budaya, 2024)
The ongoing changes brought about by time, globalization, and modernization compel individuals to adapt, significantly impacting Islamic culture worldwide. This article explores the themes, trends, and transformations of modern Islamic culture through a Systematic Literature Review methodology using Scopus. Out of 1,097 documents, 30 documents from 17 countries were analyzed. Most of these were authored by researchers from the USA, Iran, and Indonesia. Three main themes emerged from the analysis: Islamism, cultural relations, and historical perspectives. Additionally, five key themes were identified: Diverse Perspectives on Islamic Tradition, Adaptation to Modernity, Ethical and Philosophical Inquiry, Cultural and Social Dynamics, and Global-Local Interactions. The results of this study highlight the success of Muslim communities in preserving Islamic culture in the modern era while integrating Islamic values into various aspects of life, including law, arts, and sciences. This article contributes to a deeper understanding of the global phenomenon of modernization within Islamic culture.